A clinicopathological study of multinodular goitre - Athavale, Virendra S.; Thakkar, Saurabh M.; Gope, Debabrata D.; Tulsian, Akriti R.; B., Sree Kumar; Gogineni, Jyotsna C. (International Surgery Journal, 2019)
Background: Multinodular goitre (MNG) is a clinicopathological entity characterized by an increased volume of the thyroid gland with formation of nodules. The present study has been planned to study the various clinical presentations and diagnostic accuracy between operative findings and histopathological findings in a case of multinodular goitre. Methods: The present study was a hospital-based prospective study conducted in Dr D.Y. Patil Medical College, Hospital and Research Centre, Pune between July 2016 to September 2018. 100 patients aged between 15 to 75 yrs. clinically diagnosed as multinodular goitre were included. Results: FNAC finding of multinodular goitre in the study group showed colloid goitre was seen in 62 cases, 27 cases had multinodular goitre. 6 cases had neoplastic etiology, 3 cases had Hashimoto’s thyroiditis and 2 cases had papillary carcinoma of thyroid. HPE finding wise distribution showed that 10 cases were malignant, and 90 cases were benign. FNAC finding was significantly associated with histopathological finding in detecting malignant or benign lesion of multinodular thyroid gland and diagnostic accuracy of FNAC is 92%. Clinical finding comparison with operative finding showed that diagnostic accuracy of detecting malignant or benign lesion was only 35%. There was no significant difference among the two methods for detecting type of lesion in multinodular thyroid. Conclusions: Females are predominantly affected. About 8% cases of MNG are malignant. Considering the histopathological report as a gold standard, correlation of FNAC finding with histopathological finding was very much accurate and significant for detecting malignant and benign lesion of multinodular thyroid.